The complex synthesis and solid state chemistry of ceria-lanthana solid solutions prepared via a hexamethylenetetramine precipitation. - HOLMES, JUSTIN DEREK (Elsevier, 2011)
Mixed oxide solid solutions are becoming ever more commercially important across a range of applications. However, their synthesis can be problematical. Here, we show that ceria-lanthana solid solutions can be readily prepared via simple precipitation using hexamethylenetetramine. However, the solution chemistry can be complex which results in the precipitated particles having a complex structure and morphology. Great care must be taken in both the synthesis and characterisation to quantify the complexity of the product. Even very high heat treatments were not able to produce highly homogeneous materials and x-ray diffractions reveals the non-equilibrium form of particles prepared in this way. Unexpected crystal structures are revealed including a new metastable cubic La2O3 phase.
PUBLISHED
Keywords: Physical chemistry; Solid solutions